The recovery of Tabunio Watershed through enrichment planting using ecologically and economically valuable species in South Kalimantan, Indonesia - SYARIFUDDIN KADIR; BADARUDDIN BADARUDDIN; NURLINA NURLINA; ICHSAN RIDWAN; FONNY RIANAWATI (Society for Indonesian Biodiversity, 2016)
Kadir S, Badaruddin, Nurlina, Ridwan I, Rianawaty F. 2016. The recovery of Tabunio Watershed through enrichmentplanting using ecologically and economically valuable species in South Kalimantan, Indonesia. Biodiversitas 17: 140-147. Watershed isa medium system where hydrological-biophysical processes as part of hydrological cycle and social, economic, and cultural events asthe results of human intervention on natural resource occur. The increasing human population results in the increasing need of water thatmay reduce the availability of water, causing environmental degradation. The objectives of this study were to study the characteristics ofTabunio watershed and to give recommendation on the enrichment planting for the watershed recovery. This study used watershedecological area approach and the data were analyzed spatially using GIS. The results showed that based on the characteristics of itscomponents, Tabunio Watershed was categorized as moderately to very highly qualified for recovery. The recovery should be donethrough:(i) enrichment planting based on the land capability, land suitability and the legal function of the area, (ii) conservation of soil and water using vegetative and civil engineering methods, and (iii) issuance of regulations to increase the watershed’s carrying capacity.